Analisis Kebutuhan Pengembangan E-Booklet Bernuansa Kontekstual Pada Materi Virus dan Peranannya Sebagai Media Pembelajaran Elektronik Biologi Fase E di SMA Negeri 1 Kecamatan Guguak - Hasna Luthifah; Zulyusri Zulyusri (Symbiotic: Journal of Biological Education and Science, 2024)
The development of ICT has a positive impact on the learning media used. However, it was found that teachers who have not been able to develop ICT-based learning media at SMAN 1 Guguak District. These difficulties are caused by the lack of teachers' skills in utilizing ICT in learning. This study aims to describe the need to develop electronic-based learning media in the form of e-booklets with contextual nuances for Phase E students at SMAN 1 Guguak District. The e-booklet is designed concisely, systematically and given examples of the environment around students. Students will understand the benefits of the knowledge gained for their daily lives. This study uses a qualitative descriptive approach. The instruments used in the research were student questionnaires containing questions about the process and use of learning media for class XI Phase F and interview guide sheets for biology teachers of SMAN 1 Kec. The subjects of this study consisted of 60 students of Class XI Phase F and one Biology teacher of SMAN 1 Guguak District. Data analysis was carried out using a descriptive qualitative approach, which involved collecting qualitative data and providing descriptive explanations. According to research, all students need electronic learning materials such as e-booklets, and among biology course content that is considered difficult to understand, 38.8% of students cite virus materials. Furthermore, 100% of students support the use of e-booklets that provide contextual intricacies to make learning more relevant.